Answer: 6
Explanation:
3(4-2) = 3(2) = 6
Angles can be used to estimate the side lengths of a shape.
The letters in order of greatest to least are (a), (b) and (c)
The sum of angles at side (a) is:
![a = 30 + 50](https://tex.z-dn.net/?f=a%20%3D%2030%20%2B%2050)
![a = 80](https://tex.z-dn.net/?f=a%20%3D%2080)
The sum of angles at side (c) is:
![c = 50 + 90](https://tex.z-dn.net/?f=c%20%3D%2050%20%2B%2090)
![c = 140](https://tex.z-dn.net/?f=c%20%3D%20140)
The sum of angles at side (b) is:
![b = 40 + 90](https://tex.z-dn.net/?f=b%20%3D%2040%20%2B%2090)
![b = 130](https://tex.z-dn.net/?f=b%20%3D%20130)
So, we have:
![a = 80](https://tex.z-dn.net/?f=a%20%3D%2080)
![b = 130](https://tex.z-dn.net/?f=b%20%3D%20130)
![c = 140](https://tex.z-dn.net/?f=c%20%3D%20140)
The smaller the base angles, the longer the side.
Hence, the letters in order of greatest to least are (a), (b) and (c)
Read more about angles at:
brainly.com/question/11585894
Answer:
200%
Step-by-step explanation:
12 as a whole would be 100%. if you wanted to get to 24 (which would be double) you'd need to double the percentage! hope this helps
Answer:
y=x² +6
Step-by-step explanation:
This is the only 2nd-degree equation in the group: y = x² + 6. The others are linear equations.
Answer: c)
.
Step-by-step explanation:
Mean value theorem : If f(x) is defined and continuous on the interval [a,b] and differentiable on (a,b), then there is at least one number c in the interval (a,b) (that is a < c < b) such that
![\begin{displaymath}f'(c) = \frac{f(b) - f(a)}{b-a} \cdot\end{displaymath}](https://tex.z-dn.net/?f=%5Cbegin%7Bdisplaymath%7Df%27%28c%29%20%3D%20%5Cfrac%7Bf%28b%29%20-%20f%28a%29%7D%7Bb-a%7D%20%5Ccdot%5Cend%7Bdisplaymath%7D)
Given function :
Interval : [0,3]
Then, by the mean value theorem, there is at least one number c in the interval (0,3) such that
![f'(c)=\dfrac{f(3)-f(0)}{3-0}\\\\=\dfrac{3^2-0^2}{3}=\dfrac{9}{3}\\\\=3](https://tex.z-dn.net/?f=f%27%28c%29%3D%5Cdfrac%7Bf%283%29-f%280%29%7D%7B3-0%7D%5C%5C%5C%5C%3D%5Cdfrac%7B3%5E2-0%5E2%7D%7B3%7D%3D%5Cdfrac%7B9%7D%7B3%7D%5C%5C%5C%5C%3D3)
![\Rightarrow\ f'(c)=3\ \ \ ...(i)](https://tex.z-dn.net/?f=%5CRightarrow%5C%20f%27%28c%29%3D3%5C%20%5C%20%5C%20...%28i%29)
Since ![f'(x)=2x](https://tex.z-dn.net/?f=f%27%28x%29%3D2x)
then, at x=c, ![f'(c)=2c\ \ \ ...(ii)](https://tex.z-dn.net/?f=f%27%28c%29%3D2c%5C%20%5C%20%5C%20...%28ii%29)
From (i) and (ii), we have
![2c=3\\\\\Rightarrow\ c=\dfrac{3}{2}](https://tex.z-dn.net/?f=2c%3D3%5C%5C%5C%5C%5CRightarrow%5C%20c%3D%5Cdfrac%7B3%7D%7B2%7D)
Hence, the correct option is c)
.